Cost of counselling women who undergo mastectomy. Issue 6333 (26th June 1982) - Maguire, P; Pentol, A; Allen, D; Tait, A; Brooke, M; Sellwood, R
Abstract : The psychiatric morbidity associated with mastectomy and brest cancer was substantially reduced by a specialist nurse who counselled women before and after surgery and monitored their progress. A controlled study was, therefore, carried out to determine what this cost. National Health Service costs were almost wholly covered by savings made because counselled subjects who developed psychiatric problems were recognised and treated much earlier than control patients. Counselled and control subjects suffered considerable financial losses, but these were offset in the counselled group by their relatives' earlier return to work. Such counselling schemes are necessary and effective and may be implemented at little extra cost.